Transformation of Domestic Wastewater Management Policy in Malang - Marsuhin; Nur Aisyah, Sitti; Mauludin, Febri Wahyu (Badan Perencanaan Pembangunan Kota Malang, 2024)
This study reexamines the implementation of Malang City's Local Regulation No. 2 of 2017, which addresses the management of domestic wastewater. The research investigates the factors supporting and hindering the policy's execution and assesses the effectiveness of the local government's strategies. Using a qualitative approach through interviews and observations, the findings reveal that the policy fulfills several key elements necessary for successful implementation, including well-defined target groups, programs, and administrative structures. However, communication gaps and limited public understanding present challenges to full compliance. This study highlights the importance of public engagement and improved information dissemination for more sustainable wastewater management practices in urban settings.